The pros and cons of probiotic use in pediatric oncology patients following treatment for acute lymphoblastic leukemia - Šimiaková, Miroslava; Bielik, Viktor (Frontiers in Pediatrics, 2024)
Acute lymphoblastic leukemia (ALL) treatment, involving chemotherapy, radiotherapy, and pharmacotherapy (antibiotics, antineoplastics) perturbs the gut microbiota in pediatric patients, with enduring effects post-treatment. ALL treatments diminish microbial richness and diversity, favoring pathogenic bacteria. Probiotics may offer promise in mitigating these disruptions and associated side effects. This mini-review explores the impact of ALL treatment on the gut microbiota and the potential benefits of probiotics in pediatric oncology. Probiotics have shown promise in restoring gut microbial balance, reducing treatment-associated side effects, and potentially improving quality of life. However, potential adverse effects, particularly in immunocompromised patients, warrant caution. Notably, there's emerging interest in probiotics' role in bone health and mineral bioaccessibility. Further research is needed to elucidate probiotics' mechanisms and their broader impact on pediatric health. Integration of probiotics into ALL treatment and post-treatment regimens offers significant potential for improving patient outcomes and reducing treatment-related complications and long-lasting disruptions, although careful monitoring is essential.